Mechanism of Chlorination Process: From Propanoic Acid to α-Chloropropanoic Acid and Byproducts Using Propanoic Anhydride as Catalyst. (4th June 2017) - Xue, Da; Li, Yuna; Liu, Jisheng; Gao, Chuan; Xue, Jianwei; Li, Fuxiang; Lv, Zhiping
Abstract : This article reports on findings regarding the mechanism of chlorination process. In this experiment, propanoic acid was chlorinated to α -chloropropanoic acid in a lab-scale glass tube reactor operating at 130°C. Propanoic anhydride and concentrated sulfuric acid were, respectively, used as the catalyst and the promoter. This experiment adopted the DFT method to calculate the activation energy of routes for the synthesis α -chloropropanoic acid, β -chloropropanoic acid, α, α -dichloropropanoic acid, and α, β -dichloropropanoic acid. The results showed that the main route of α -chloropropanoic acid was formed through an ionic mechanism when propanoic anhydride was used as the catalytic agent. Activation energy of 1-propen-1-ol, 1-chloro, which was formed from 1-prop-anol, 1-chloro-, was the highest in the process of ionic mechanism. In addition, α, α -dichloropropanoic acid was formed via a consecutive ionic chlorination path from α -chloropropanoic acid. β -Chloropropanoic acid was produced from propanoic acid through a chlorination radical mechanism. α, β -Dichloropropanoic acid was formed via a consecutive radical chlorination path.